الاعتبارات الإنسانيّة المانعة من تنفيذ العقوبات الشّرعيّة - قرازة, مراد; بوكركب, عبد المجيد (جامعة الوادي - University of Eloued, 2021)
في هذا المقال حاولنا الردّ على من يشغّب على أحكام الشّريعة الإسلاميّة، بوصف العقوبات المقرّرة فيها بالقسوة، وعدم اعتبارها لحقوق الإنسان الأساسيّة، فسلّطنا فيه الضّوء على نموذج من نماذج سماحة الإسلام في مجال القضاء الجنائي؛ وذلك بإبراز الاعتبارات الإنسانيّة الكثيرة الّتي راعاها المسلمون أثناء تطبيق هذه العقوبات، مراعيا في ذلك مذهب الجمهور من علماء المسلمين، وأئمّة المذاهب الأربعة، دون اعتبار لمن شذّ عن الصفّ وخالف الجماعة، حتّى يكون للمقال مصداقيّة في عين المخالف. وقد توصّلنا إلى أنّ الفقه الإسلامي في هذا الباب يزخر بالشّواهد الدّالّة على عموم رحمة اللّه، وواسع إحسانه، ويعجّ بالأحكام والتّفاصيل الّتي شُرعت حماية لحقوق الإنسان الأساسيّة، وحفظت حاجاته الضّرورية؛ فلم تشرع عقوبة إلاّ على مستحقّها، ولم تنفّذ إلاّ على الوجه المراد بها، فلا تقام في الإسلام عقوبة على حامل أو مرضع إلاّ بضمان حقّ جنينها وولدها، ولا تنفّذ بمريض أو نفساء إلا باعتقاد سلامته بعدها، ولا تجرى وقت حرّ أو قرّ مخافة أن يهلك الجاني معها، ويجري اعتبار جميع ذلك إمّا بتأخير العقاب حتّى تتوافر ظروفه، أو تخفيفه حتّى تؤمن عواقبه. This article attempts to counter the claims which remonstrate the Islamic Shariaa law and condemn its penal code as being violent and inconsistent with fundamental human rights. Therefore, we shed light on one of the samples representing the tolerance of Islam in criminal judiciary through highlighting the countless humanitarian considerations attentively regarded by Muslim scholars when it comes to the application of this penal code, taking into account the perspective of the majority (al-jomhoor) of the Muslim scholars and the Imams of the four schools (Madhhabs), and withdrawing those who deviated from the Ijma’a, in order to reach a certain level of credibility. We have concluded that the Islamic jurisprudence contains in this area a large body of clear evidence on the mercy of Allah and His immense beneficence; we have reached as well that it is full of rules and details that confirmed men’s rights and preserved their necessary needs. For instance, a sentence can never be performed to a pregnant or a nursing mother without securing the child’s life rights; nor can it be performed to an ill or a mother in puerperium until his safety is confirmed after, as it can’t be performed when the weather is too hot or too cold for fear that the child may be affected. In such cases, the sequence is delayed until it is a better time, or commuted to avoid other fatal consequences.
Humanitarian considerations that prevent the implementation of legal punishments
مقال
Keywords: العقوبات الشّرعيّة ; تنفيذ العقوبة ; موانع العقاب؛ ; حقوق الإنسان ; الجريمة; the crime; legal punishment; sentence execution; punishment impediments; human rights